Manguezal do estuário Barra Grande em Icapuí-CE: da degradação ao processo de recuperação e mudança de atitude - Silva, José de Arimatea da (2012)
The research conducted in Barra Grande, Icapuí – CE analyzed in a systematic way the geo environmental aspects of Barra Grande estuary with emphasis on mangrove and other coastal systems associated with it. The methodological foundations were related to the definition of the dynamic processes by identifying flows of matter and energy of the geo environmental diagnosis to highlight the importance of the mangrove estuary and in the maintenance of other coastal ecosystems and biodiversity. In this process, a space-time analysis was made through the preparation of thematic maps and charts showing the occupation of mangrove by economic activities generating impacts (salt, fish and shrimp) that led to environmental degradation and impairment of the ecosystem and its biodiversity. We also analyzed the social mobilization initiatives and environmental education process that arose from the joints of youth groups and NGOs that triggered political and environmental movements in Icapuí generators of change of attitude toward the use and conservation of mangroves. Also noteworthy is the implementation of projects for the rehabilitation of degraded areas and conservation of the wetland, identified and analyzed to provide data for interpreting the potential for social mobilization for the conservation of lowland environmental systems under study. Finally, the research allowed the development of a proposed environmental zoning of the estuary and mangrove swamp, with reference to the demarcation proposed by the Municipal Law No. 298/2000 which established the Environmental Protection Area (EPA) of Barra Grande.